2022
DOI: 10.1038/s41598-022-23357-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating thrombospondin 2 levels reflect fibrosis severity and disease activity in HCV-infected patients

Abstract: Among several secreted glycoproteins belonging to the thrombospondin family, thrombospondin 2 (TSP2) is involved in various functions, including collagen/fibrin formation. Liver/serum TSP2 levels have been correlated to liver fibrosis stage and disease activity in nonalcoholic fatty liver disease. This study investigated whether serum TSP2 was associated with clinicopathological features in hepatitis C virus (HCV)-infected patients as well. A total of 350 patients with HCV who had undergone liver biopsy were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…Notably, we found that the reductions in serum TSP2 levels only correlated with improvements in liver stiffness, but not with those in HbA1c, BW and hepatic steatosis. Our findings, together with previous studies demonstrating the prognostic significance of baseline circulating TSP2 level in predicting more advanced stages of hepatic fibrosis, 1,8–10 suggested that circulating serum TSP2 level is a potential promising novel hepatic fibrosis biomarker capable of reflecting changes in hepatic fibrosis, and could be further developed as another noninvasive tool for monitoring the severity of hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Notably, we found that the reductions in serum TSP2 levels only correlated with improvements in liver stiffness, but not with those in HbA1c, BW and hepatic steatosis. Our findings, together with previous studies demonstrating the prognostic significance of baseline circulating TSP2 level in predicting more advanced stages of hepatic fibrosis, 1,8–10 suggested that circulating serum TSP2 level is a potential promising novel hepatic fibrosis biomarker capable of reflecting changes in hepatic fibrosis, and could be further developed as another noninvasive tool for monitoring the severity of hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 74%
“…[5][6][7] Circulating TSP2 was recently identified as a potential novel biomarker of hepatic fibrosis. 1,[8][9][10] In morbidly obese individuals, higher circulating TSP2 levels were associated with increasing severity of hepatic steatosis, inflammation and fibrosis. 1,8 In T2D patients with coexisting NAFLD, baseline circulating TSP2 level was associated with the presence and the development of advanced hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar ndings were reported from other groups, thus corroborating the ability of TSP2 to estimate disease activity and brosis stage in NAFLD 8 7 . In addition, we earlier reported that serum TSP2 levels re ected brosis severity and disease activity in HCV-infected patients 5 . Based on this accumulating evidence, we hypothesized that a correlation between TSP2 and liver disease activity could also be present in hepatitis B.…”
Section: Discussionmentioning
confidence: 97%
“…17,18 Furthermore, a correlation between the degree of fibrosis and inflammation and serum TSP2 levels was observed not only in NAFLD, but also in hepatitis C virus-infected patients. 19,20 Despite these advances, however, the specific liver cell populations responsible for THBS2/TSP2 expression in NAFLD, the underlying mechanisms governing expression dynamics, and the precise role of THBS2/TSP2 in the pathogenesis of NAFLD remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%